IDENTIFICATION OF CAUSES OF DEMAND VARIATION AND ITS IMPACT ON SALES VOLUME - AN EXPLORATORY STUDY IN PROCESSED FOOD INDUSTRY IN BANGLADESH - Fazle Rabbi; Tanvir Ahmed; Anup Saha; Pallab Sutradhar (European Scientific Journal, ESJ, 2013)
Demand variation is a key issue in processed food industry, because demands for processed food products vary daily. The organizations in this situation face challenges to meet customer demand. Their products have a definite shelf life and prone to be obsolete. Obsolete products are totally wastes. So, there exists a producer risk. This study has been conducted with the aim of identifying the root causes of demand variation and its impact on sales volume. For this purpose an exploratory study involving two food processing organizations and their forty eight points of sales had been performed. Each food item has different causes and consequences for demand variation. In this regard, three food items having limited shelf life had been selected to find out the causes of their demand variation. The study identified eleven causes and twelve consequences such as special occasion, duration of shelf life, wrong forecasting and so on. Then some root causes are figured out that dominates over others. The impacts of these causes on sales volume are also shown with six months demand data. The research concludes with the level of impact of the significant causes like price, occasion. Lastly some recommendations are mentioned to minimize those root causes of demand variation.